Design and Implementation of an IoT-Based Smart Greenhouse Monitoring System Prototype Using ESP32 Microcontroller - Laoli, Christoper Alfredo; Ongku Puadi Harahap; Arga Sakti Oktavianus Sihombing; Eka Dodi Suryanto; Dian Putra Saragi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of Internet of Things (IoT) technology provides solutions to improve the efficiency of monitoring and managing plant environments, particularly in greenhouse systems. A common problem is the lack of optimal monitoring of environmental conditions such as temperature, air humidity, soil moisture, and light intensity, which significantly affect plant growth. This study aims to design and implement a prototype smart greenhouse monitoring system based on IoT using the ESP32 microcontroller to monitor environmental conditions in real-time and support automatic irrigation. The research method used is an experimental approach involving system design, assembly, and testing in an indoor environment using potted plants. The system utilizes a DHT11 sensor for temperature and humidity, a soil moisture sensor for soil conditions, an LDR sensor for light intensity, and an ultrasonic sensor for measuring water level. The collected data were analyzed descriptively to evaluate system performance. The results show that all sensors function properly and are able to detect environmental changes accurately, and the system successfully transmits data in real-time to a monitoring platform. The implication of this research is that the developed system can serve as an effective solution for automated plant monitoring and irrigation in small to medium-scale applications.